Exploring the role of endogenous retroviruses in seasonal reproductive cycles: a case study of the ERV-V envelope gene in mink - Zhang, Yufei; Wang, Gaofeng; Zhu, Yanzhu; Cao, Xiaodong; Liu, Fang; Li, Huiping; Liu, Shuying (Frontiers in Cellular and Infection Microbiology, 2024)
Endogenous retroviruses (ERVs), which originated from exogenous retroviral infections of germline cells millions of years ago and were inherited by subsequent generations as per Mendelian inheritance patterns, predominantly comprise non-protein-coding sequences due to the accumulation of mutations, insertions, deletions, and truncations. Nevertheless, recent studies have revealed that ERVs play a crucial role in diverse biological processes by encoding various proteins.In this study, we successfully identified an ERV envelope (env) gene in a mink species.A phylogenetic tree of mink ERV-V env and reference sequences was constructed using Bayesian methods and maximum-likelihood inference. Phylogenetic analyses indicated a significant degree of sequence conservation and positive selection within the env-surface open reading frame. Additionally, qRT-PCR revealed diverse patterns of mink ERV-V env expression in various tissues. The expression of mink ERV-V env gene in testicular tissue strongly correlated with the seasonal reproductive cycles of minks. Our study suggests that the ERV-V env gene in mink may have been repurposed for host functions.